Open innovation and entrepreneurship: A review from the perspective of sustainable business models - Jiayi Huang; Peng Zhou (Cardiff University, Cardiff Business School, 2025)
Open innovation serves as a critical pathway for aligning Sustainable Business Models (SBMs) with the dual imperatives of the sustainable economy and the digital economy. This editorial review synthesizes insights from theoretical frameworks, particularly the Resource-Based View (RBV) and Transaction Cost Theory (TCT), integrated with the Technology-Organization-Environment (TOE) framework to explore the mechanisms driving open innovation. Our editorial review highlights key dimensions influencing open innovation: technology (digital platforms, emerging technologies like AI, IoT, and blockchain), organization (stakeholder collaboration, governance mechanisms), and environment (regulatory frameworks, market dynamics, and industrial spillovers). This unified framework offers actionable insights for policymakers to foster enabling ecosystems and for business leaders to adopt open innovation strategies for resource optimization and governance improvement. The review concludes that the RBV-TCT-TOE framework provides a generalizable and robust tool for understanding and advancing open innovation across industries and regions, bridging theoretical and practical dimensions to address the challenges of sustainability and digital transformation.
Keywords: 330; Open Innovation; Entrepreneurship; Sustainable Business Model